Pengelolaan Sarana dan Prasarana untuk Meningkatkan Pembelajaran Siswa - Sholihan Sholihan (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
The existence of facilities and infrastructure at MTs NU Menara is very influential in supporting the quality of student learning. With the availability of facilities and infrastructure in educational institutions, it can make it easier for students and teachers to carry out learning activities. Adequate facilities and infrastructure such as the availability of a library can be used by students to help support teaching and learning activities. The use of facilities and infrastructure is well utilized by the teacher with the LCD in the classroom so that learning is more effective and not boring. MTs NU Menara is a madrasa with limited facilities and infrastructure. The learning system applied by the teacher in the classroom is not only based on textbooks that only use the lecture system but often also utilizes existing facilities and infrastructure in madrasas such as LCDs and the use of libraries so that learning is more interesting and not boring. Facilities and infrastructure at MTs NU Menara, which have limitations, do not necessarily eliminate infrastructure just like that. As for the means used in the removal of this item, it is very rarely done because items such as benches and chairs have a durable nature. At MTs NU Menara, items are deleted at least once every 5 years, even if there are items to be deleted. This study aims 1) to determine the implementation of facilities and infrastructure management in supporting the quality of student learning at MTs Nu Menara, Gunungteguh Village, Sangkapura District. 2) find out what are the supporting and inhibiting factors for the implementation of facilities and infrastructure management in supporting the quality of student learning at MTs Nu Menara, Gunungteguh Village, Sangkapura District. The method used in this research is a descriptive qualitative method. the data collection techniques used are observation, interview, and documentation techniques. The data analysis technique used is reduction, data display, and conclusion drawing. The results of this study indicate that: 1) the completeness of adequate facilities and infrastructure will facilitate the learning process so that it is more effective and efficient in carrying out teaching and learning activities. 2) the supporting and inhibiting factors in the quality of this learning are from within the madrasa itself, namely the availability of adequate facilities and infrastructure so that it can support the learning process, while the inhibiting factors include lack of funds, in addition to the lack of awareness of students in maintaining facilities and infrastructure in madrasas this is due to the lack of a sense of belonging to students in using these facilities and infrastructure.